Relationship marketing and satisfaction of external users of three dental centers specialized in Pediatric Dentistry. Lima, 2019 - Solís Romero, Denny Liliana (2021)
Objective: Analyze the association between relationship marketing and the satisfaction of external users of three dental centers specialized in pediatric dentistry in Lima during 2019 last semester. Material and Methods: The sample size was made up of 150 external users from three pediatric dentistry centers, to whom two questionnaires were applied, one on external user satisfaction and the other on relationship marketing, both were adapted and validated for use through the judgment of ten experts with Aiken’s V and reliability in a pilot study with Cronbach’s Alpha. The instruments were made up of twenty questions each with Likert-type scale evaluations. Results: 76% of the sample were women and 24% men; the average ages were 39.67 ± 6.93 and42.08 ± 6.89 years; respectively. The three dental centers presented a good level of relationship marketing and global satisfaction. There is an association between the dimensions of relationship marketing and the level of satisfaction of external users in the three dental centers (Chi-Square Test; p <0.05). Conclusions: There is an association between relationship marketing and the satisfaction of external users in the three Pediatric Dentistry centers and between the dimension of trust, commitment, loyalty, and communication of relationship marketing and the level of satisfaction of external users in the three centers.